Identifying meteorological factors influencing catechin biosynthesis and optimizing cultivation conditions of tea plant (Camellia sinensis) - Tukhvatshin, Marat; Peng, Qiliang; Zhao, Xuan; Liu, Jianghong; Xiang, Ping; Lin, Jinke (Frontiers in Plant Science, 2025)
Catechins, the most important bioactive components in tea plants (Camellia sinensis), are influenced by the growth environment. To identify and optimize the key meteorological factors affecting catechin accumulation, we investigated the relationship between meteorological factors and tea plant catechin biosynthesis across three growing seasons at 10 locations. Rainfall, average temperature, and effective accumulated temperature (EAT) were identified as key drivers regulating catechin accumulation via the responsive expression of key structural genes CsCHS1, CsANR, and CsSCPL. Optimal meteorological conditions for enhancing total esterified catechins (TEC) and total non-esterified catechins (TNEC) were determined using LINGO software, although the optimal conditions for these two groups were contrasting. Hot and rainy environments promote the biosynthesis of EGCG, ECG, and TEC through CsPAL and CsSCPL, while reduced rainfall and EAT promote the accumulation of C, EGC, and TNEC. This study reveals the differential effects of meteorological factors on catechin accumulation and obtains optimal meteorological conditions for promoting catechin accumulation. These results provide guidance for improving catechin accumulation and tea cultivation management.